2018
DOI: 10.1007/s10554-018-1442-x
|View full text |Cite
|
Sign up to set email alerts
|

Is there any diagnostic value of anteroposterior chest radiography in predicting cardiac chamber enlargement?

Abstract: The anteroposterior (AP) portable chest radiograph is routinely performed to evaluate cardiopulmonary status, however heart size can be misrepresented by inherent technical factors. Our aim was to determine diagnostic accuracy of cardiothoracic ratio (CTR) on AP chest radiographs relative to echocardiography, as well as relative to axial computed tomography (CT) and frontal CT scout images in predicting cardiac chamber enlargement. 200 subjects with both chest CT and AP chest radiograph within 1 month were ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Earlier studies already demonstrated that the CTR could be a prognostic factor for myocardial enlargement in various illnesses [ 29 , 30 , 31 , 32 ]. Values >0.55 were considered incorrect for radiographs in the AP projection [ 25 , 26 ], and the same value was demonstrated in a study investigating the dependence between CTR in the AP projection and heart measurements in computed tomography [ 33 ].…”
Section: Discussionmentioning
confidence: 97%
“…Earlier studies already demonstrated that the CTR could be a prognostic factor for myocardial enlargement in various illnesses [ 29 , 30 , 31 , 32 ]. Values >0.55 were considered incorrect for radiographs in the AP projection [ 25 , 26 ], and the same value was demonstrated in a study investigating the dependence between CTR in the AP projection and heart measurements in computed tomography [ 33 ].…”
Section: Discussionmentioning
confidence: 97%